(untitled) (Journal of Information Technology and Digital World, 2023)
Many industries require a certain amount of electrical power. Prepaid metering, with its unique performance in the Internet of Things (IoT), tends to be an efficient power management system by providing cost-effective prepaid electricity services to the industrial sector. Errors can occur at any stage of the energy billing process, including errors in electromechanical meters, human errors during meter reading, and errors in processing paid and unpaid bills. A prepaid energy meter is the solution to these problems. In this work, prepaid energy meters were developed to reduce energy consumption in the industry. The introduction of this prepaid meter will contribute to improving energy management, saving energy, and eliminating fraudulent billing. Automated billing systems track consumption in real time, eliminating the possibility of fraudulent billing and consumption disputes. A prepaid energy meter was developed using current and voltage sensors, and the energy meter was tested with a load connected to a 220 V power supply. Energy meters are connected to the cloud to create a user alert system.